Generation of self-excited jet oscillations at a wedge - Vovk, I. V.; Malyuga, V. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The problem of a submerged jet running around a rigid wedge is studied numerically. We consider both the transient process of jet oscillation initiation and the sustained self-excited jet oscillations.